Position of Local Wisdom Values of Balinese Indigenous People in the Policy - Astara, Wayan Wesna (Opción, 2019)
The aim of the study is to investigate the position of local wisdom values of Balinese indigenous people in the policy via a qualitative method with anthropological and sociological approaches. The findings show that Balinese indigenous people through social-religious organizations (traditional villages) can manage management of tourist villages in Bali by using modern management by increasing human resources in traditional values-based traditional villages in Bali with village Awig-awig laws adat. In conclusion, the importance of managing traditional village-based tourist villages provides opportunities for indigenous villages to increase human resources in the management of tourist villages.